(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2012)
The Retail Sector of Indian Economy is going through the phase of tremendous transformation. The retail sector of Indian economy is categorized into two segments such as organized retail sector and unorganized retail sector. In Indian retailing sector the larger share of the retail market is captured by unorganized sector. Currently, India is the 5th largest retail market in the world. The market size in 2010 was estimated at US 353 bn (Source: IBEF) and is expected to reach US 543 bn by 2014. There are many factors which are contributing the growth of retail sector such as increase per capita income and living standard, easy and low cost credit facilities, change in consumption pattern, improvements in infrastructure, availability of retail space and sources of financing. The proposed paper would try to find out the factor, which are contributing in growth of retail sector in India. We would also try to compare the foreign and Indian retailing sector in terms of total share of organized and unorganized retail sector, Consumption spending and growth rate. The paper would also try to explain current and future trends in retail sector in India.